Innovative strategies to promote global health: Lessons from the Covid-19 pandemic - Andrew John Macnab (GHMJ (Global Health Management Journal), 2023)
The current view is that the hold of the Covid-19 virus is now being altered from pandemic to endemic status with global cooperation. While vaccination remains a central component of the public health interventions required to achieve this, a range of innovative health promotion strategies are also needed in parallel if we are to ensure that the pandemic continues to wane further. Research and personal experience tell us that Covid-19 vaccines offer high protection against severe illness, aid the delivery of health care and save lives. However, WHO communiqués reiterate that vaccine hesitancy is a major threat to global health and that many countries still need to improve vaccination rates. It is also stated that in order to do this innovative strategies are needed to establish greater trust, improve communication and reduce misinformation. Consequently health care providers are being urged to build on lessons learned during the pandemic, find ways to build trust, counter residual vaccine hesitancy and promote other health related behaviors that are inclusive, allay fears and avoid scapegoating. Importantly, the strategies needed to increase willingness to be vaccinated and promote the health-related knowledge and behaviors necessary for the pandemic to continue to wane are now known to be highly country-specific, and regional differences in what approaches are required are also evident within counties. Consequently, as health care providers we need to develop innovative strategies and employ task shifting to the meet the specific needs of the individual populations we serve. This review summarizes ways to approach this challenge based the core principles advocated by WHO for promoting health literacy and changing behaviors; community empowerment, people-centered strategies, innovative education, novel and improved tools, training to respond to local needs, and the use of non-traditional avenues and outlets.